Remote Center of Motion (RCM) Mechanisms for Surgical Operations - Serhat AKSUNGUR (International Journal of Applied Methods in Electronics and Computers, 2015)
Nowadays, surgical applications, entering the body through a small incision with laparoscopic procedures are performed and are expanding the use of robots for these operations. In existing systems, conventional robots are used for the body. Surgical procedure is carried out by a separate mechanism which is attached to the end of the robot and robot is used to positioning this mechanism. These mechanisms are called Remote Center of Motion (RCM) mechanism. In this paper, the literature on studies performed about the parallel, spherical and hybrid RCM mechanisms are examined and classified.